Screening of bacteriophages for subsequent treatment of resistant Escherichia coli infections transmitted through poultry - Mobeen ur Rashid; Saeed Ahmed; Javed Muhammad; Muhammad Tariq Navid; Waseem Safdar; Aman Karim; Ijaz Ahmad; Haider Ali; Kashif Abdaal (Brazilian Journal of Microbiology, 2026)

Eco-engineered Cu–Fe bimetallic nanoparticles via Cotula australis extract: RSM-driven optimization for enhanced catalytic dye removal - Muhammad Irfan; Aman Rabia; Bashir Farzana; Ahmad Tausif; Yumna Sadef; Abdul Mannan Hafiz; Muhammad Nawaz (Nanotechnology for Environmental Engineering, 2026)

Opioidergic and GABAergic mechanisms underlie the anti-nociceptive effects of adamantane amino thiazole derivatives: synthesis, toxicity evaluation and mechanistic insights using standard pre-clinical models - Urooj Aman; Gowhar Ali; Atteeque Ahmed; Aamer Saeed; Mushtaq Ahmad Mir; Nasreena Bashir; Asma Khurshid; Muhammad Ayaz (Inflammopharmacology, 2026)

Performance assessment of nature-based solutions for sustainable urban housing - Muhammad Aarish Shah; Syed Hassaan Ali Shah; Omama Zeb; Aman Alam (Energy and Buildings, 2026)

Insights into Diagenetic Evolution and Paleoenvironment of Eocene Jatta Gypsum in the Kohat Basin, Pakistan - Hassanat Ullah; Qiu Longwei; Muhammad Kashif; Pavel Smirnov; Pelin Güngör Yeşilova; Shahab Aman-e-room; Khalid Ali Khan (Carbonates and Evaporites, 2026)

Eco-friendly rapeseed protein-chitosan hybrid nanocomposite films for active food packaging and preservation - Frage Abookleesh; Muhammad Zubair; Aman Ullah (Food Hydrocolloids, 2026)

Keratin-derived bio-adsorbents for water remediation: Current and future trends - Muhammad Zubair; Zahid Rauf; Aman Ullah (Bioresource Technology Reports, 2026)

Energy-Efficient, Multi-Agent Deep Reinforcement Learning Approach for Adaptive Beacon Selection in AUV-Based Underwater Localization - Zahid Ullah Khan; Hangyuan Gao; Farzana Kulsoom; Syed Agha Hassnain Mohsan; Aman Muhammad; Hassan Nazeer Chaudry (Journal of Marine Science and Engineering, 2026)
Accurate and energy-efficient localization of autonomous underwater vehicles (AUVs) remains a fundamental challenge due to the complex, bandwidth-limited, and highly dynamic nature of underwater acoustic environments. This paper proposes a fully adaptive deep reinforcement learning (DRL)-driven localization framework for AUVs operating in Underwater Acoustic Sensor Networks (UAWSNs). The localization problem is formulated as a Markov Decision Process (MDP) in which an intelligent agent jointly optimizes beacon selection and transmit power allocation to minimize long-term localization error and energy consumption. A hierarchical learning architecture is developed by integrating four actor–critic algorithms, which are (i) Twin Delayed Deep Deterministic Policy Gradient (TD3), (ii) Soft Actor–Critic (SAC), (iii) Multi-Agent Deep Deterministic Policy Gradient (MADDPG), and (iv) Distributed DDPG (D2DPG), enabling robust learning under non-stationary channels, cooperative multi-AUV scenarios, and large-scale deployments. A round-trip time (RTT)-based geometric localization model incorporating a depth-dependent sound speed gradient is employed to accurately capture realistic underwater acoustic propagation effects. A multi-objective reward function jointly balances localization accuracy, energy efficiency, and ranging reliability through a risk-aware metric. Furthermore, the Cramér–Rao Lower Bound (CRLB) is derived to characterize the theoretical performance limits, and a comprehensive complexity analysis is performed to demonstrate the scalability of the proposed framework. Extensive Monte Carlo simulations show that the proposed DRL-based methods achieve significantly lower localization error, lower energy consumption, faster convergence, and higher overall system utility than classical TD3. These results confirm the effectiveness and robustness of DRL for next-generation adaptive underwater localization systems.

Palladium-catalyzed Suzuki–Miyaura and Buchwald–Hartwig cross-coupling reactions towards the synthesis of pharmacologically potent pyrimidine-based molecules - Fatima Aman; Labiqa Aman; Nasir Rasool; Mahwish Arshad; Muhammad Imran; Ayesha Malik; Sana Iqbal (Molecular Diversity, 2026)

Fluorescence Interface Engineering of PEDOT: PSS–HTL and BPhen–ETL Layers in Alq₃-Based OLEDs for Biomedical Applications - Ghazi Aman Nowsherwan; Hafiz Muhammad Khubaib; Muhammad Azhar; Saira Riaz; Shahzad Naseem (Journal of Fluorescence, 2025)

A functional self-assembled layer with preferential sodium adsorption sites for ultra-stable sodium metal batteries - Moazzam Ali; Asif Mahmood; Muhammad Ali; Samia Aman; Hamid Hussain; Xuan Zhang; Yinzhu Jiang; Xufeng Lin; Muhammad Yousaf (Chemical Engineering Journal, 2025)

Comparative study on effect of Pleurotus florida treated and untreated wheat straw on feed intake, digestibility, and growth rate in cattle calves - Muhammad Tahir Khan; Haq Aman Ullah; Ihtisham Ul Haq; Maria Munir; Syeda Maryam Hussain; Muhammad Mushtaq; Nazir Ahmad Khan (Tropical Animal Health and Production, 2025)

Enhancing underwater acoustic orthogonal frequency division multiplexing based channel estimation: a robust convolution-recurrent neural network framework with dynamic signal decomposition - Mansoor Jan; Muhammad Aman; Syed Agha Hassnain Mohsan; Samih M. Mostafa; Faten Khalid Karim (Frontiers in Marine Science, 2025)
Introduction Underwater acoustic (UWA) communication systems confront significant challenges due to the unique, dynamic, and unpredictable nature of acoustic channels, which are impacted by low signal-to-noise ratio (SNR), severe multipath propagation, latency, Doppler spread, and a shortage of real-world data. Orthogonal frequency division multiplexing (OFDM) is essential for establishing resilient and reliable data transmission in these challenging environments, but accurate channel estimation remains a critical barrier to unlocking its full potential—especially given the limitations of conventional estimation methods in adapting to UWA channel dynamics. Methods This work introduces a Convolution-Recurrent Neural Network (CRNet) estimator integrated with dynamic signal decomposition (DSD) techniques (e.g., Local Mean Decomposition, LMD; Empirical Mode Decomposition, EMD) to estimate UWA-OFDM channel characteristics and mitigate noise-induced distortions in received signals. The CRNet architecture combines convolutional layers (to capture spatial features) and recurrent layers (to model temporal dependencies), enabling it to learn complex UWA channel dynamics. The model is trained using paired data: received pilot symbols, transmitted pilots, and accurate channel impulse responses (CIR). Post-training, CRNet operates using only the received signal as input, eliminating the need for supplementary channel characteristics like SNR. To ensure real-world relevance, training and testing datasets are generated via the Bellhop ray-tracing model, which simulates diverse UWA environments (shallow coastal and continental shelf). Results Numerical findings demonstrate that the proposed CRNet model consistently outperforms benchmark methods—including least squares (LS), minimal mean square error (MMSE), and backpropagation neural network (BPNN)—across key metrics: bit error rate (BER), amplitude error, and phase error. CRNet exhibits superior performance with QPSK modulation compared to QAM, and maintains robustness even with a small number of pilot symbols. Performance evaluations on both training and unseen datasets confirm its resilience and flexibility in demanding UWA environments, validating its ability to generalize to dynamic channel conditions beyond training scenarios. Discussion The CRNet estimator addresses critical limitations of conventional UWA-OFDM channel estimation methods: its dual focus on spatial and temporal features (via convolutional-recurrent layers) overcomes the static linear constraints of LS/MMSE, while DSD-driven noise mitigation enhances input signal quality for more accurate estimation. By eliminating reliance on post-training supplementary channel data (e.g., SNR), CRNet simplifies real-world deployment. Its superior BER performance and adaptability to diverse UWA environments (shallow coastal, continental shelf) position it as a robust solution for improving the reliability and efficiency of UWA communication systems.

Cobalt-doped manganese oxide nanoparticles and their composite with titanium oxide nanocomposite: Photocatalysts with tuned band gap for enhanced visible-light-driven dye degradation - Syed AminUllah; Safia Hassan; Zahid Imran; Mohammed Aman; Muhammad I. Masud; Sumra Afzal (Journal of Water Process Engineering, 2025)

PM2.5 pollution and its correlation with meteorological parameters over the four capital cities of Pakistan - Bahadar Zeb; Jawad Nasir; Khan Alam; Allah Ditta; Muhammad Arif Aman; Muhammad Shafiq (Environmental Monitoring and Assessment, 2025)

The role of mentorship in veterinary practice: An empirical study of the Animal Health Mentoring Framework in Pakistan - Ujala Fatima Shan; Aneela Zameer Durrani; Muhammad Zahid Iqbal; Shakera Sadiq Gill; Esha Binte Iqbal; Sadia Sanaullah; Muhammad Aftab; Mahrukh Ahmed; Safdar Aman (The Veterinary Journal, 2025)

Feather keratin-based hybrid adsorbents: Reproducibility and efficacy in metal removal from synthetic wastewater - Irum Zahara; Muhammad Faisal Irfan; Tariq Siddique; Aman Ullah (Journal of Water Process Engineering, 2025)

Evolutionary history of microgastrine wasps (hymenoptera: braconidae: microgastrinae) in Sundaland: insights from Peninsular Malaysia - Ameyra Aman-Zuki; Muhamad Azmi Mohammed; Aqilah Sakinah Badrulisham; Muhammad Ikhwan Idris; Mohd Fuat Salbi; Salmah Yaakop (International Journal of Tropical Insect Science, 2025)

Leveraging machine learning for the optimization of reinforced rapeseed protein-gelatin edible coatings for enhanced food preservation - Frage Abookleesh; Muhammad Zubair; Aman Ullah (Chemical Engineering Journal, 2025)

Advanced upcycling of spent hen lipids using engineered-enzymatic cascade - Elias Rietzschel; Kethmi Jayawardhane; Muhammad Zubair; Guanqun Chen; Aman Ullah (Biocatalysis and Agricultural Biotechnology, 2025)

Global progress towards the Coal: Tracking coal reserves, coal prices, electricity from coal, carbon emissions and coal phase-out - Muhammad Amir Raza; Abdul Karim; M.M. Aman; Mahmoud Ahmad Al-Khasawneh; Muhammad Faheem (Gondwana Research, 2025)

Corrigendum to “Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices” [Fuel 336 (2023) 127066] - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2025)

Spatiotemporal pattern of climatic water balance over Balochistan, Pakistan for the period 1961–2016 - Muhammad Qasim; Kamal Ahmed; Aman Jan; Najeebullah Khan; Atif Muhammad Ali (Theoretical and Applied Climatology, 2025)

FeS-based nanocomposites: A promising approach for sustainable environmental remediation – Focus on adsorption and photocatalysis – A review - Aqsa Nawaz; Aman Khalid; Wajeeha Qayyum; Rabia Bibi; Muhammad Azam Qamar; Muhammad Zahid; Ahmad Farhan; Manoj P. Rayaroth; Łukasz Cichocki; Grzegorz Boczkaj (Journal of Environmental Management, 2025)

Conservation agriculture effects on ecosystem health and sustainability – A review of rice–wheat cropping system - Muhammad Farooq; Ahmad Nawaz; Abdul Rehman; Aman Ullah; Abdul Wakeel; Hafeez ur Rehman; Ahmad Nawaz; Kadambot H.M. Siddique; Michael Frei (Science of The Total Environment, 2024)

Corrigendum to “Coral like gadolinium doped hematite nanostructure as stable and robust electrocatalyst for oxygen evolution water splitting” [Fuel 338 (2023) 127313] - Mehar Un Nisa; Soumaya Gouadria; Sara Houda; Karam Jabbour; Sumaira Manzoor; Salma Aman; Muhammad Najam-Ul-Haq; Muhammad Naeem Ashiq (Fuel, 2024)

Salt Stress in Wheat: Effects, Tolerance Mechanisms, and Management - Muhammad Farooq; Noreen Zahra; Aman Ullah; Faisal Nadeem; Abdul Rehman; Riti Kapoor; Mawra S. Al-Hinani; Kadambot H.M. Siddique (Journal of Soil Science and Plant Nutrition, 2024)

Emerging paradigms in two-dimensional materials: Classification, synthesis, and the role of defects in electrocatalysis for water splitting and oxygen reduction reaction - Muhammad Sajid; Muhammad Azam Qamar; Ahmad Farhan; Wajeeha Qayyum; Aman Khalid; Aqsa Nawaz; Shern-long Lee; Haq Nawaz (Journal of Environmental Chemical Engineering, 2024)

Exogenously Applied γ-Aminobutyric Acid Improves Salt Tolerance in Alfalfa by Modulating Ion Homeostasis, Proline Accumulation and Antioxidant Defence System - Safaa Mohammed Al-Farsi; Aman Ullah; Abdullah M. Al-Sadi; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2024)

Designing and synthesis of perovskite nanocrystals: a promising wide-spectrum solar light–responsive photocatalyst and lead ion sensor - Nisar Ali; Shakeel Ahmad; Arif Nawaz; Manzoor Khan; Aman Ullah; Muhammad Idrees; Adnan Khan; Wilayat Khan (Environmental Science and Pollution Research, 2024)

Long-Term Follow-Up of Cerebral Aneurysms Completely Occluded at 6 Months After Intervention with the Woven EndoBridge (WEB) Device: a Retrospective Multicenter Observational Study - Kareem El Naamani; Panagiotis Mastorakos; Nimer Adeeb; Mathews Lan; James Castiglione; Omaditya Khanna; Jose Danilo Bengzon Diestro; Rachel M. McLellan; Mahmoud Dibas; Justin E. Vranic; Assala Aslan; Hugo H. Cuellar-Saenz; et al. (Translational Stroke Research, 2024)

Mapping the low tolerance factor Bi(Li1/3Zr2/3)O3 end member and MPB composition nexus in Bi1/2Na1/2TiO3-based ceramics - Sabir Ali; Muhammad Sheeraz; Aman Ullah; Won Seok Yun; Amir Ullah; Ill Won Kim; Chang Won Ahn (Chemical Engineering Journal, 2024)

Empirical analysis of cost-effective and equitable solid waste management systems: Environmental and economic perspectives - Asif Iqbal; Abdullah Yasar; Abdul-Sattar Nizami; Rafia Haider; Imran Ali Sultan; Aman Anwer Kedwaii; Muhammad Murtaza Chaudhary; Muhammad Hassan Javed; Anees Ahmad; Khadija Sajid; Muhammad Naqvi; Muhammad Usman Ghori (Environmental Research, 2024)

Progress in layered double hydroxides (LDHs): Synthesis and application in adsorption, catalysis and photoreduction - Ahmad Farhan; Aman Khalid; Nimra Maqsood; Sidra Iftekhar; Hafiz Muhammad Adeel Sharif; Fei Qi; Mika Sillanpää; Muhammad Bilal Asif (Science of The Total Environment, 2024)

Hydrothermal synthesis of ZnO@MoTe2 nanocomposite as excellent electrocatalyst for hydrogen evolution reaction (HER) - Saeed D. Alahmari; Salma Aman; Soumaya Gouadria; Sajjad Ahmad Khan; Abdullah G. Al-Sehemi; A.M.A. Henaish; Naseeb Ahmad; Zubair Ahmad; Taha Abdel Mohaymen Taha; Hafiz Muhammad Tahir Farid (Fuel, 2024)

Oxalic acid: A blooming organic acid for postharvest quality preservation of fresh fruit and vegetables - Mahmood Ul Hasan; Zora Singh; Hafiz Muhammad Shoaib Shah; Jashanpreet Kaur; Andrew Woodward; Eben Afrifa-Yamoah; Aman Ullah Malik (Postharvest Biology and Technology, 2023)

Friedelin and Glutinol induce neuroprotection against ethanol induced neurotoxicity in pup’s brain through reduction of TNF-α, NF-kB, caspase-3 and PARP-1 - Marva Sandhu; Hafiz Muhammad Irfan; Laiba Arshad; Aman Ullah; Shahid Ali Shah; Hussain Ali (NeuroToxicology, 2023)

Recent advances in chitosan-based materials; The synthesis, modifications and biomedical applications - Yasir Iqbal; Iqbal Ahmed; Muhammad Faisal Irfan; Shahzad Ali Shahid Chatha; Muhammad Zubair; Aman Ullah (Carbohydrate Polymers, 2023)

Inclusion of the fungus Pleurotus florida in the diet affects performance and feed efficiency traits in calves: a case study on Ravi buffalo - Muhammad Tahir Khan; Nazir Ahmad; Nazir Ahmad Khan; Haq Aman Ullah; Saif Ullah (Tropical Animal Health and Production, 2023)

Correction to: The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Removal of divalent cations and oxyanions by keratin-derived sorbents: Influence of process parameters and mechanistic studies - Irum Zahara; Muhammad Faisal Irfan; Muhammad Zubair; Tariq Siddique; Aman Ullah (Science of The Total Environment, 2023)

Co-application of Biochar and Seed Priming with Nano-sized Chitosan-Proline Improves Salt Tolerance in Differentially Responding Bread Wheat Genotypes - Marwa Sulaiman Al Hinai; Aman Ullah; Al-Khaleel M. Al-Toubi; Ibtisam Rashid Al Harrasi; Ahlam Ali Alamri; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Application of Nano Chitosan-glycinebetaine for Improving Bread Wheat Performance under Combined Drought and Heat Stresses - Muna Hamed Khalid Al Masruri; Aman Ullah; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Food waste: causes and economic losses estimation at household level in Pakistan - Samina Khalid; Aman Ullah Malik; Muhammad Irfan Ullah; Muhammad Shafique Khalid; Hafiz Muhammad Rashad Javeed; Muhammad Asif Naeem; Aqsa Naseer (Environmental Science and Pollution Research, 2023)

The Woven EndoBridge (WEB) Device for the Treatment of Intracranial Aneurysms: Ten Years of Lessons Learned and Adjustments in Practice from the WorldWideWEB Consortium - Adam A. Dmytriw; Mahmoud Dibas; Sherief Ghozy; Nimer Adeeb; Jose Danilo Bengzon Diestro; Kevin Phan; Hugo H. Cuellar-Saenz; Ahmad Sweid; Sovann V. Lay; Adrien Guenego; Leonardo Renieri; Ali Al Balushi; et al. (Translational Stroke Research, 2023)

Characteristics and prediction of paleo-environment of Eocene Jatta Gypsum, Kohat Basin, Pakistan - Hassanat Ullah; Zhong Jianhua; Muhammad Kashif; Shahab Aman e Room; Zeeshan Zafar; Saif Ur Rehman (Arabian Journal of Geosciences, 2023)

Coral like gadolinium doped hematite nanostructure as stable and robust electrocatalyst for oxygen evolution water splitting - Mehar Un Nisa; Soumaya Gouadria; Sara Houda; Karam Jabbour; Sumaira Manzoor; Salma Aman; Muhammad Najam-Ul-Haq; Muhammad Naeem Ashiq (Fuel, 2023)

Uniformly dispersed flowery EuZrSe3 derived from the europium-based metal–organic framework for energy storage devices - Abdul Ghafoor Abid; Soumaya Gouadria; Sumaira Manzoor; Khadijah Mohammed Saleh Katubi; Karam Jabbour; Muhammad Abdullah; Mehar Un Nisa; Salma Aman; Mohammed Sultan Al-Buriahi; Muhammad Naeem Ashiq (Fuel, 2023)

Thiourea Application Increases Seed and Oil Yields in Camelina Under Heat Stress by Modulating the Plant Water Relations and Antioxidant Defense System - Muhammad Ahmad; Ejaz Ahmad Waraich; Usman Zulfiqar; Aman Ullah; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2023)

Sodium and Chloride Sensitivity in Alfalfa (Medicago sativa L.): Growth, Photosynthesis, and Tissue Ion Regulation in Contrasting Genotypes - Safaa Mohammed Al-Farsi; Abdullah M. Al-Sadi; Aman Ullah; Muhammad Farooq (Journal of Plant Growth Regulation, 2023)

Urinary PAHs metabolites in Karakoram Highway’s heavy traffic vehicle (HTV) drivers: evidence of exposure and health risk - Maria Rafique; Audil Rashid; Shu Tao; Bin Wang; Aman Ullah; Lun Lu; Habib Ullah; Muhammad Ubaid Ali; Waqas Naseem (Environmental Geochemistry and Health, 2023)

Defective nickel zirconium oxide mesoporous bifunctional electrocatalyst for oxygen evolution reaction and overall water splitting - Maira Sadaqat; Sumaira Manzoor; Salma Aman; Laraib Nisar; Muhammad Najam-Ul-Haq; Afzal Shah; Ahmed M. Shawky; H. Elhosiny Ali; Muhammad Naeem Ashiq; T.A. Taha (Fuel, 2023)

Evaluation of aerobic biodegradation of phenanthrene using Pseudomonas turukhanskensis: an optimized study - Monika Sharma; El-Sayed Salama; Muhammad Usman; Aman Khan; Muhammad Arif; Xiangkai Li (Biodegradation, 2023)

Renewable energy production from novel and non-edible seed oil of Cordia dichotoma using nickel oxide nano catalyst - Rozina; Mushtaq Ahmad; Nasib Qureshi; Muhammad Zafar; Sher Aman Ullah; Sheikh Zain Ul Abidin (Fuel, 2023)

Nitrogen Pollution Originating from Wastewater and Agriculture: Advances in Treatment and Management - Muhammad Usman; Muhammad Sanaullah; Aman Ullah; Shun Li; Muhammad Farooq (Reviews of Environmental Contamination and Toxicology, 2022)

On nonlinear dynamics of COVID-19 disease model corresponding to nonsingular fractional order derivative - Muhammad Arfan; Maha M. A. Lashin; Pongsakorn Sunthrayuth; Kamal Shah; Aman Ullah; Kulpash Iskakova; M. R. Gorji; Thabet Abdeljawad (Medical & Biological Engineering & Computing, 2022)

Corporate social responsibility and patient’s intention to revisit: A serial mediation study witnessing the healthcare sector - Attia Aman-Ullah; Anis Ali; Waqas Mehmood; Muhammad Fareed; Attiqa Aman-Ullah (Environmental Science and Pollution Research, 2022)

Plant Growth and Fruit Quality Response of Strawberry is Improved After Exogenous Application of 24-Epibrassinolide - Muhammad Moaaz Ali; Raheel Anwar; Aman Ullah Malik; Ahmad Sattar Khan; Saeed Ahmad; Zahoor Hussain; Mahmood Ul Hasan; Mudassar Nasir; Faxing Chen (Journal of Plant Growth Regulation, 2022)

Addressing the Directionality Challenge through RSSI-Based Multilateration Technique, to Localize Nodes in Underwater WSNs by Using Magneto-Inductive Communication - Gang Qiao; Aman Muhammad; Muhammad Muzzammil; Muhammad Shoaib Khan; Muhammad Owais Tariq; Muhammad Shahbaz Khan (Journal of Marine Science and Engineering, 2022)
The deployment and efficient use of wireless sensor networks (WSNs) in underwater and underground environments persists to be a difficult task. In addition, the localization of a sensor Rx node in WSNs is an important aspect for the successful communication with the aforementioned environments. To overcome the limitations of electromagnetic, acoustic, and optical communication in underwater and underground wireless sensor networks (UWSNs), magneto-inductive (MI) communication technology emerged as a promising alternative for usage in UWSNs with a wide range of applications. To make the magneto-inductive underwater wireless sensor networks (MI-UWSNs) more efficient, recently, various research studies focused on the optimization of the physical layer, MAC layer, and routing layer, but none of them has taken into account the effect of directionality. Despite the directionality issue posed by the physical nature of a magnetic field, the unique qualities of MI communication open up a gateway for several applications. The directionality issue of MI sensors is a critical challenge that must be taken into account while developing any WSN protocol or localization algorithm. This paper highlights and discusses the severity and impact of the directionality issue in designing a localization algorithm for magneto-inductive wireless sensor networks (MI-WSNs). A received signal strength indicator (RSSI)-based multilateration localization algorithm is presented in this paper, where a minimum of 2 and maximum of 10 anchor Tx nodes are used to estimate the position of the sensor Rx nodes, which are deployed randomly in a 15 m × 15 m simulation environment. This RSSI-based multilateration technique is the most suitable option that can be used to quantify the impact of directionality on the localization of a sensor Rx node.

First report on molecular surveillance based on duplex detection of Anaplasma marginale and Theileria annulata in dairy cattle from Punjab, Pakistan - Farhan Ahmad Atif; Rao Zahid Abbas; Saba Mehnaz; Muhmmad Fiaz Qamar; Kashif Hussain; Muhammad Usman Nazir; Muhammad Arfan Zaman; Aman Ullah Khan; Mourad Ben Said (Tropical Animal Health and Production, 2022)

Bread Wheat Genotypes Accumulating Free Proline and Phenolics Can Better Tolerate Drought Stress Through Sustained Rate of Photosynthesis - Aman Ullah; Waleed M. Al-Busaidi; Abdullah M. Al-Sadi; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2022)

Gibberellic acid and urease inhibitor optimize nitrogen uptake and yield of maize at varying nitrogen levels under changing climate - Ikram Ullah; Khadim Dawar; Muhammad Tariq; Muhammad Sharif; Shah Fahad; Muhammad Adnan; Haroon Ilahi; Taufiq Nawaz; Mukhtar Alam; Aman Ullah; Muhammad Arif (Environmental Science and Pollution Research, 2022)

Sonolytic-ozonation technology for sanitizing microbial contaminants and pesticide residues from spinach (Spinacia oleracea L.) leaves, at household level - Zarghona Siddique; Aman Ullah Malik; Muhammad Rafique Asi; Raheel Anwar; Muhammad Inam Ur Raheem (Environmental Science and Pollution Research, 2021)

Wheat Genotypes with Higher Intercellular CO2 Concentration, Rate of Photosynthesis, and Antioxidant Potential Can Better Tolerate Drought Stress - Aman Ullah; Rashid Said Al-Rajhi; Abdullah M. Al-Sadi; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2021)

Low temperature and hypoxic conditions induce flavonoids biosynthesis and enhances antioxidant potential of crabapple (Malus profusion) fruits - Rana Naveed Ur Rehman; Sajid Ali; Mahmood Ul Hasan; Raheel Anwar; Muhammad Wasim Haider; Ahmad Sattar Khan; Aman Ullah Malik; Li Pengmin (Acta Physiologiae Plantarum, 2021)

Salt Tolerance in Alfalfa Landraces of Omani Origin: Morpho-Biochemical, Mineral, and Genetic Diversity Assessment - Safaa Mohammed Al-Farsi; Abdullah M. Al-Sadi; Aman Ullah; Muhammad Farooq (Journal of Soil Science and Plant Nutrition, 2021)

Zinc Application in Combination with Zinc Solubilizing Enterobacter sp. MN17 Improved Productivity, Profitability, Zinc Efficiency, and Quality of Desi Chickpea - Aman Ullah; Muhammad Farooq; Faisal Nadeem; Abdul Rehman; Mubshar Hussain; Ahmad Nawaz; Muhammad Naveed (Journal of Soil Science and Plant Nutrition, 2020)

Pulses Production in Pakistan: Status, Constraints and Opportunities - Aman Ullah; Tariq Mahmud Shah; Muhammad Farooq (International Journal of Plant Production, 2020)

Study of occupational exposure to brick kiln emissions on heavy metal burden, biochemical profile, cortisol level and reproductive health risks among female workers at Rawat, Pakistan - Mehwish David; Qurat-Ul-Ain; Muhammad Afzal; Muhammad Shoaib; Faiza Aman; Karen J. Cloete; Naheed Turi; Sarwat Jahan (Environmental Science and Pollution Research, 2020)

Evaluation of indigenous Omani alfalfa landraces for morphology and forage yield under different levels of salt stress - Safaa Mohammed Al-Farsi; Saleem K. Nadaf; Abdullah M. Al-Sadi; Aman Ullah; Muhammad Farooq (Physiology and Molecular Biology of Plants, 2020)

Characterization and synthetic biology of lipase from Bacillus amyloliquefaciens strain - Muhammad Tahir Khan; Aman Chandra Kaushik; Qurrat ul ain Rana; Shaukat Iqbal Malik; Anwar Sheed Khan; Dong-Qing Wei; Wasim Sajjad; Shabir Ahmad; Sajid Ali; Ameenullah; Muhammad Irfan (Archives of Microbiology, 2020)

Bioavailability and Speciation of Heavy Metals in Polluted Soil as Alleviated by Different Types of Biochars - Weijie Xu; Shuzhen Hou; Yaqian Li; Muhammad Aman Khan; Wenxuan Luo; Zhenhua Chen; Yongqing Li; Xiangdong Wu; Zhengqian Ye; Dan Liu (Bulletin of Environmental Contamination and Toxicology, 2020)

Recent advances in protein derived bionanocomposites for food packaging applications - Muhammad Zubair; Aman Ullah (Critical Reviews in Food Science and Nutrition, 2020)

First report of post-harvest rot of Citrus reticulata cv. ‘Kinnow’ caused by Rhizopus arrhizus in Pakistan - Anam Moosa; Ayaz Farzand; Shahbaz Talib Sahi; Sajid Aleem Khan; Aman Ullah Malik; Mark Lawrence Gleason; Binyamin Rana; Muhammad Amjad Ali (Journal of Plant Pathology, 2020)

Predicting Down syndrome and neural tube defects using basic risk factors - Momina T. Khattak; Eko Supriyanto; Muhammad N. Aman; Rania H. Al-Ashwal (Medical & Biological Engineering & Computing, 2019)

Nickel toxicity in plants: reasons, toxic effects, tolerance mechanisms, and remediation possibilities—a review - Muhammad Umair Hassan; Muhammad Umer Chattha; Imran Khan; Muhammad Bilal Chattha; Muhammad Aamer; Muhammad Nawaz; Abid Ali; Muhammad Aman Ullah Khan; Tahir Abbas Khan (Environmental Science and Pollution Research, 2019)

First report of Alternaria alternata causing postharvest fruit rot of peach in Pakistan - Muhammad Waqar Alam; Abdul Rehman; Aman Ullah Malik; Sidra Aslam; Mubeen Sarwar; Sajid Ali; Muhammad Arslan Khan; Akhtar Hameed; Sohaib Sarfraz (Journal of Plant Pathology, 2019)

Whole exome sequencing identified two novel homozygous missense variants in the same codon of CLCN7 underlying autosomal recessive infantile malignant osteopetrosis in a Pakistani family - Muhammad Aman Khan; Aman Ullah; Muhammad Naeem (Molecular Biology Reports, 2018)

Manganese nutrition improves the productivity and grain biofortification of fine grain aromatic rice in conventional and conservation production systems - Aman Ullah; Muhammad Farooq; Asif Nadeem; Abdul Rehman; Saeed A. Asad; Ahmad Nawaz (Paddy and Water Environment, 2017)

Production of α-1,4-glucosidase from Bacillus licheniformis KIBGE-IB4 by utilizing sweet potato peel - Muhammad Asif Nawaz; Zainab Bibi; Asad Karim; Haneef Ur Rehman; Muhsin Jamal; Tour Jan; Afsheen Aman; Shah Ali Ul Qader (Environmental Science and Pollution Research, 2017)

Influence of Metal-Resistant Rhizobacteria on the Growth of Helianthus annuus L. in Cr(VI)-Contaminated Soil - Ali Bahadur; Aftab Afzal; Rizwan Ahmad; Fahad Nasir; Aman Khan; Vishandas Suthar; Gul Jan; Asfa Batool; Muhammad Amir Zia; Muhammad Mahmood-ul-Hassan (Water, Air, & Soil Pollution, 2016)

Dietary mycotoxins binders: a strategy to reduce aflatoxin m1 residues and improve milk quality of lactating Beetal goats - Haq Aman Ullah; Aneela Zameer Durrani; Muhammad Ijaz; Aqeel Javeed; Umer Sadique; Zahoor Ul Hassan; Altaf Ur Rahman; Muqader Shah; Irfan Khattak (Journal of Consumer Protection and Food Safety, 2016)

Synthesis and structural elucidation of two new series of aurone derivatives as potent inhibitors against the proliferation of human cancer cells - Aboubaker A. Elhadi; Hasnah Osman; Muhammad Adnan Iqbal; Sharmila K. Rajeswari; Mohamed B. Khadeer Ahamed; Amin M.S. Abdul Majid; Mohd Mustaqim Rosli; Ibrahim Abdul Razak; Aman Shah Abdul Majid (Medicinal Chemistry Research, 2015)

Extraction, Cleanup, and Chromatographic Determination of Imidacloprid Residues in Wheat - Sajid Iqbal; Riaz Uddin; Sumayya Saied; Mubarik Ahmed; Muhammad Abbas; Sahar Aman (Bulletin of Environmental Contamination and Toxicology, 2012)

Purification and Characterization of Novel α-Amylase from Bacillus subtilis KIBGE HAS - Saeeda Bano; Shah Ali Ul Qader; Afsheen Aman; Muhammad Noman Syed; Abid Azhar (AAPS PharmSciTech, 2011)